Development of Low Fat Mayonnaise Using Whey Protein as a Natural Emulsifier - Tri Umar Satriawan; Herly Evanuarini; Imam Thohari (Faculty of Animal Science Universitas Brawijaya, 2022)
Mayonnaise is an oil-in-water emulsion product that uses egg yolk as a stabilizer agent. Low-fat mayonnaise is made as a product modification to make it healthier by reducing fat. whey protein concentrate is given as a natural emulsifier. The objective of this study was to determine the effect of whey protein concentrate addition on low-fat mayonnaise based on carbohydrates, ash, fat content and emulsion droplets. The material used in this study was vegetable oil, and the addition of whey protein concentrate. This research used was a laboratory experimental method with a completely randomized design with 4 treatments and 5 replications. The treatments using control treatment without the addition of whey protein concentrate and treatment using whey protein concentrate as much as 5%, 10%, and 15% of the total use of oil. The variables measured were carbohydrate, ash, fat, antioxidants and emulsion droplets. The results showed that the use of whey protein concentrate in mayonnaise gave highly significant difference (p<0.01) in carbohydrate and fat content, gave a significantly different result (p<0.05) in the ash content, didn’t gave significant difference (p>0.05) in antioxidants and gave a highly significant difference (p<0.01) in the length of the emulsion droplet diameter so that it looked uniform in shape and size. The conclusion of this study is the use of whey protein concentrate as much as 15% produces the best low-fat mayonnaise